2020
DOI: 10.1101/2020.11.04.368217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphonate production by marine microbes: exploring new sources and potential function

Abstract: Phosphonates, organic compounds with a C-P bond, constitute 20-25% of phosphorus in high molecular weight dissolved organic matter and are a significant phosphorus source for marine microbes. However, little is known about phosphonate sources, biological function, or biogeochemical cycling. Here, we determine the biogeographic distribution and prevalence of phosphonate biosynthesis potential using thousands of genomes and metagenomes from the upper 250 meters of the global ocean. Potential phosphonate producer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 112 publications
(170 reference statements)
0
15
0
Order By: Relevance
“…Modeled dFe was averaged over 12 months at a 0.5 degree grid in 5 m 3/23 depth bins from the upper 250 meters. Metagenome sequence data and associated metagenomes with environmental variables were quality controlled as described earlier [34,35].…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeled dFe was averaged over 12 months at a 0.5 degree grid in 5 m 3/23 depth bins from the upper 250 meters. Metagenome sequence data and associated metagenomes with environmental variables were quality controlled as described earlier [34,35].…”
Section: Data Sourcesmentioning
confidence: 99%
“…All Prochlorococcus genomes were searched for siderophore biosynthesis potential using antiSMASH v5.0 [42], which searches for known non-ribosomal peptide synthetases and polyketide synthase siderophore biosynthesis pathways. The true proportion of genomes with the siderophore transport cluster was estimated by accounting for genome incompleteness in the single-cell genomes as described earlier [34].…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they are ubiquitous in terrestrial and aquatic ecosystems [10][11][12][13][14] . Phosphonates also represent a major fraction of the marine organic phosphorus pool 11,[15][16][17] and recent studies have now identified several cosmopolitan marine microorganisms capable of synthesising significant quantities of these compounds 6,7,9,18,19 . Collectively, this synthesis drives a vast global oceanic phosphorus redox cycle with reduced phosphorus input in the surface ocean estimated to be an order of magnitude greater than pre-anthropogenic riverine phosphorus input 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging evidence suggests that Pi-insensitive 2AEP catabolism occurs in nature 22,23 . Notably, the absence of 2AEP from otherwise phosphonate rich high molecular weight (HMW) DOM 16,17 , despite its supposed ubiquitous production 9,19,24,25 , suggests preferential catabolism of this molecule in comparison to alkylphosphonates.…”
Section: Introductionmentioning
confidence: 99%